PERAN CLASSIC TOURS DALAM PROMOSI PAKET WISATA SASAK TUR DESA SADE MELALUI SOSIAL MEDIA - Akhmad Matra Hadi; Suparwi Suparwi; Afiefah Sulistyowati (Jurnal Perhotelan dan Pariwisata, 2025)
Sade Village in Central Lombok has significant potential as a cultural tourism destination, yet the effectiveness of its promotion depends heavily on the digital strategies adopted by travel industry stakeholders. This study aims to analyze the role of Classic Tours in promoting the Sasak Tour travel package of Sade Village through social media from the customer perspective and to identify the forms of creative content employed. The research applied a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that Classic Tours utilizes various digital channels, particularly Blogspot, Facebook, email, and WhatsApp, to expand information outreach, enhance interactions, and build customer relationships. Promotional content focuses on clear product descriptions, supporting visuals, and accessible contact information, which effectively increase tourist interest, strengthen the company’s image, and maintain customer loyalty. The study concludes that consistent digital promotion strategies enhance the appeal of Sade Village as a cultural tourism destination; however, expansion to other popular platforms such as Instagram and YouTube is recommended to better engage younger market segments. The practical implication highlights that creative content-based digital promotion can serve as an effective model for tourism businesses in developing culture-based destinations.